Editorial: Understanding Women’s Lives and Trauma Through Narrative Research and Analysis - Bojko , Dr. Martha (East European Journal of Psycholinguistics, 2021)
Welcome to this special issue titled “Women’s Life and Trauma in Individual and Collective Narratives” of the East European Journal of Psycholinguistics. Narratives, both oral and written, play an important role in helping the individual make sense of their lives and the world they live in. Narrative research is focused on the elicitation and interpretation of people’s narrative accounts of their lived experiences. In recent decades, there has been an enormous growth in the use of narrative inquiry and narrative-based research with diverse theoretical orientations and methodologies grounded in various disciplines of the social sciences and humanities including anthropology, psychology, psycholinguistics, sociology, history and literary studies as well as in medicine and clinical research (Chase, 2005, 2011; Holstein & Gubrium, 2012; Kleinman, 1988; Charon, 2006). According to Chase (2005), most narrative researchers treat narrative as a distinctive form of discourse that shapes meaning through the concerted ordering of story material with speakers providing particular understandings of personal action and experiences by organizing events and objects into meaningful patterns, connecting subjects, actions, events, and their consequences over time.As narrative research has become increasingly complex and rigorous, this special issue was planned to gain insight into the narrative research being conducted by international scholars with a focus on women and trauma, broadly defined. The call for papers attracted many high-quality submissions from authors representing various countries. The special issue contains a collection of ten papers, each providing a unique perspective and understanding of trauma in women’s lives and its reflection in narrative inquiry. Just as women’s voices are varied, so too are the narratives presented. Women are represented as narrators; as subjects of the narration and as characters in the narrative. The authors also present a broad spectrum of approaches to the empirical analysis of narrative material ranging from social media content, life stories, clinical and educational interventions, and literary works.  In the first paper of the special issue, Bifulco’s article seeks to explore links between selected investigative child abuse interview accounts using narratives elicited through the Childhood Experience of Care and Abuse (CECA) clinical interview guide and analyzed using the Linguistic Inquiry and Word Counts (LIWC) text analysis program (Francis & Pennebaker, 1992) which identifies characteristics of speech associated with trauma. Her paper examines the potential of combining these approaches to systematically analyze and interpret trauma narratives.In the second article, the contextual backdrop for the narratives is the COVID-19 pandemic. In her article, Kostruba analyzes narratives collected online to gain an understanding of how specific social restrictions, stay-at-home orders particular to the pandemic affected all aspects of life including psychological well-being. Her study also used LIWC psycholinguistic analysis of these current pandemic narratives to identify markers of traumatic experience and identify possible gender differences in the ways women experienced (and continue to experience) the COVID-19 global pandemic.The importance of social and cultural context is apparent in the next article which draws on literary texts as the source material. For Aguilar Lopez & Miguel Borge, the drama The Golden Ribbon by María Manuela Reina, written and situated in the 1980s, a decade that for Spain implied a more obvious abandonment of the most traditional conceptions of the role of women, serves as the unit of analysis. The authors describe the divergent worldview models of the older versus younger characters, reflecting both a generational and gender divide around topics such as success, infidelity, and matrimony. Aguilar Lopez & Miguel Borge aim to identify if, how and why the dramatist is able to reach out to the general public through her play to create social awareness and give voice to the women who rebelled against the traditional social and gender roles.The next paper in this series focuses on the emerging field of post-traumatic growth (PTG) defined by Tedeschi & Calhoun (2004) as a “positive psychological change experienced as a result of the struggle with highly challenging circumstances.” Drawing on therapeutic narratives from women participating in a psychotherapy workshop, Lushyn & Sukhenko utilize dialectical understanding and discourse analysis to identify and assess the women’s descriptions and definitions associated with post-traumatic development and growth with a further attempt to provide practical implications for psychological practice.A set of the articles (#5-7) in this special issue target traumas associated with transition, be it gender transition or women and girls transitioning to another life phase (adolescence; menopause) and the emotional, social and cultural experiences connected to these transitions.Martynyuk’s article combines methodological tools of conceptual metaphor theory and narrative psychology with theoretical assumptions of the intersubjective psycholinguistic approach to meaning making and exploring transgender transition narrative metaphors. Her dataset consists of 16 TED talks videos by transgender individuals discussing their experiences of transitioning which provide Martynyuk the opportunity to conduct a narrative and visual analysis of the metaphors that are given coherence by the textual, social, cultural, and historical context of the narrative, as well as by the interactive situational context reflected in the video recordings.The article by Nair & George puts the menopausal woman as the focus of the narrative inquiry. The authors interviewed a group of male spouses about their knowledge, attitudes and beliefs about perimenopause and their experiences associated with the physical, psychological, and social changes occurring in the lives of their wives. The menopausal transition can be a period of stress, even lead to trauma if left unnoticed or unsupported. Nair & George used qualitative data software to analyze the interview data and thematic analysis to arrive at themes which could inform programs which could raise awareness about the perimenopausal and menopausal life stages of women to help both partners understand and cope with the individual, family and societal changes which occur during this life period.On the opposite end of the life spectrum, Shirazi et al, investigate whether narrative-based interventions in the school context can increase children’s emotional intelligence (EI) and whether oral and written narrative elements have a different effect on students' EI. The underlying premise is that children share their emotional experiences through narratives and stories and high-quality narratives are beneficial for children’s wellbeing and development. The research project was conducted with almost one hundred 12-year old Iranian girls who attend Yasuj city schools in southwestern Iran. Results highlighted the importance of oral and combined oral/written language modes and their merged narrative elements on the development of emotional intelligence, particularly for children who are in the language minority.The final set of articles (#8-10) make use of nostalgia and intergenerational narratives of historical trauma.Todorova & Padareva-Ilieva apply an interdisciplinary and multimodal approach to describe and classify written messages and images collected through social media in Bulgaria during the COVID-19 pandemic crisis. Findings revealed that much of the communications through social media during that period was largely nostalgic and that the main role of the Facebook social media platform is to unite people in times of isolation, to raise their spirit and save them from the traumatic experience they may encounter during a global health crisis.Zaporozhets & Stodolinska analyze the concept of border through a content analysis of the Little House children’s book series which are narrated from the lived experiences and perspective of the author Laura Ingalls Wilder based on her childhood in a settler and pioneer family in the United States in the late 1800s.  The territorial and metaphorical borders depicted in Wilder’s works are interwoven and influenced by her reminiscences of historical, biographical, gender, and psychological peculiarities.This journal issue concludes with a cross-cultural analysis of narrative reflections associated with two 20th century genocides: the Holodomor in Ukraine (1932-1933), and the Holocaust (1939-1944). Zasiekina et al recruited second (“mothers”) and third (“daughters”) generations of Holodomor and Holocaust descendants in Ukraine and Israel to share their family narratives and experiences of the genocide. The study applied inductive thematic analyses that progressed from description to interpretation, and showed the centrality of five emerging themes in both mothers’ and daughters’ narratives. The findings of their research have important implications for future practice of creating narratives with survivors of massive trauma and their offspring and stress the importance of creating a traumatic narrative to aid the healing process resulting from the transmission of historical and collective trauma and provides direction for clinical providers in designing treatment plans for individuals with genocide in their life history.In summary, the articles that make up this special journal issue reinforce the view that narrative research and inquiry provides researchers and clinicians multiple lenses and approaches through which to analyze and interpret narrative data. The subsequent results of each narrative analysis can give voice to a broad range of women and girls, while at the same time guide policy and inform educational interventions and therapeutic programs.